Examining the Low Women Autonomy in Household Decision Makings in Sidama Zone, Southern Ethiopia - Eyasu, Regassa; Nigatu, Regassa (Journal of Women's Reproductive Health, 2016)
The low level of women autonomy and the key pre disposing factors affecting household decision makings among many population groups in Ethiopia is not well understood among scholars, and is less investigated. This study examined the status and the micro level factors associated with women autonomy in Sidama, the most populous zone in Southern Ethiopia. A simple random sampling technique (using the available complete listing of households) was used to select the 231 sample households from one of the districts of the zone. Sidama zone was selected due to its historically strong customs of patriarchal family system. Quantitative and qualitative data were obtained using structured questionnaire and focus group discussions. Household, women and husband characteristics were used as explanatory variables while women autonomy index, developed from a set of questions, served as the dependent variable. The study revealed that women’s decision makings on core household and personal issues were very low in the study population. The predicted probability, using Ordinary Least Square Regression shows that women’s education, alcohol intake by husbands, household size and land size were the main determinants of autonomy in decision makings in the study area. The study recommended that concerned bodies should capitalize on educating women and girls through both formal and informal learning platforms, promote income generation activities through entrepreneurship, increased access to property and economic assets, training, microfinance and markets.
Keywords: Women autonomy; decision makings; households; Sidama Zone; Southern Ethiopia.